Failure through Success: Co-construction Processes of Imaginaries (of Participation) and Group Development - Anna Froese; Natalie Mevissen (Science, Technology, & Human Values, 2020)
Participation is an important but little understood concept in science and innovation. While participation promises the production of new knowledge, social justice, and economic growth, little research has been done on its contribution to innovation processes at the group level. The concept of imaginaries can provide a window into these processes. Adopting a micro-sociological perspective, we examined the interplay between imaginaries of participation and group development within a long-term ethnographic observation study of an initiative, Energy Avant-garde, as it pursued the development of a decentralized, self-contained, and entirely renewable energy system in one German region. We scaled down the macrolevel concept of imaginaries to the group level. We found that group imaginaries are a resource for bringing order to a group and that a group is a resource for creating, operationalizing, revising, and sustaining imaginaries. We describe a “failure-through-success” story: while imaginaries initially promoted group cohesion, creativity, and productivity, in later stages, these effects were impeded by group dynamics. We therefore distinguish between process imaginaries and outcome imaginaries and conclude that, inherently, participation must be managed and employed at the appropriate stages to make valuable contributions.
Keywords: 330; imaginaries of participation; heterogeneous innovation; energy transition; renewable energies; group creativity; co-creation